Factors associated with delay in care–seeking for fatal neonatal illness in the Sylhet district of Bangladesh: results from a verbal and social autopsy study - Bareng AS Nonyane 1,2; Narjis Kazmi 1 ,; Alain K Koffi 1; Nazma Begum 2; Salahuddin Ahmed 2; Abdullah H Baqui 1,2; Henry D Kalter 1 (Journal of Global Health, 2016)
We conducted a social and verbal autopsy study to determine cultural–, social– and health system–related factors that were associated with the delay in formal care seeking in Sylhet district, Bangladesh.